Hubungan Tingkat Pendidikan dengan Strategi Koping Warga Binaan Pemasyarakatan di Lapas Kelas II B Brebes - Fijianto, Dwi; Rejeki, Herni; Aryati, Dyah Putri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The number of prisoners in the world is increasing every year and Indonesia ranks fifth in the world. Correctional institutions in Indonesia are largely overloaded from capacity. This is a stressor for the prisoners. The educational levels of prisoners very widely, allowing the use of different coping strategies. The purpose of this study was to analyze the relationship between the level of education and the Coping Strategy of prisoners.Methods: The research design used was descriptive correlative study. Determination of the sample using purposive sampling to prisoners in Class II B Brebes Correctional institutions. Two instruments were used, namely the demographic data questionnaire and the Brief COPE questionnaire. Analysis of the frequency distribution for the univariate test and the pearson correlation test for bivariate analysis in order to describe the description of the relationship between education level and the coping strategy of prisoners.Results: The results showed that the level of education with the dimensions of problem focused coping has a correlation coefficient of 0.226 with a p value = 0.034. The education level variable with emotional focused coping has a correlation coefficient of 0.648 with a p value = 0.000, which means that there is a significant correlation between the prisoners education level variable with the dimensions of problem focused coping and emotional focused coping.Conclusion: The conclusion of the study is a significant correlation between the level of education and the coping strategy of prisoners.